A Percolative Approach to Reliability of Thin Film Interconnects and Ultra-thin Dielectrics. Issue 1 (2001) - Pennetta, C.; Reggiani, L.; Trefán, Gy.; Cataldo, R.; De Nunzio, G.
Abstract : Degradation of thin film interconnects and ultra-thin dielectrics is studied within a stochastic approach based on a percolation technique. The thin film is modelled as a two-dimensional random resistor network at a given temperature and its degradation is characterized by a breaking probability of the single resistor. A recovery of the damage is also allowed so that a steady-state condition can be achieved. The main features of experiments are reproduced. This approach provides a unified description of degradation and failure processes in terms of physical parameters.